Plasma oxylipin profile of postpartum dairy cows categorized into different systemic inflammatory grades in the first week after parturition - J.M. Grantz; A. Mukhopadhyay; A.H. Jannasch; C. Ferreira; P.R. Menta; V.S. Machado; R.C. Neves (JDS Communications, 2024)
Abstract:: Oxygenated polyunsaturated fatty acids (oxylipins) are important mediators of inflammation ranging from pro- to anti-inflammatory actions. Research investigating differences in the oxylipin profile of dairy cows suffering from different degrees of systemic inflammation in the early postpartum period is lacking and can help advance knowledge on potential mechanisms leading to excessive inflammation. The objective of this preliminary study was to evaluate the plasma oxylipin profile of cows classified in 1 of 4 systemic inflammation categories based on plasma haptoglobin (Hp) concentrations assessed on days in milk (DIM) 1, 2, 3, 4, 5, and 7, in addition to the presence or absence of metritis within 10 DIM, and of cows without any clinical diseases within 21 DIM. Groups were classified as follows: (1) cows with a peak Hp concentration ≤3 DIM (EarlyHp) and diagnosed with metritis; (2) cows with a peak Hp concentration 3 < DIM ≤7 (LateHp) and diagnosed with metritis; (3) cows suffering from persistently elevated Hp concentrations assessed on DIM 4 and 7 while remaining apparently healthy during the first 21 DIM (PersistentHp); and (4) apparently healthy cows not suffering from persistently elevated Hp concentrations (LowHp). Six cows from each category were randomly selected from a plasma bank of a parent cohort study including 380 multiparous cows. Plasma samples on DIM 1 and 2, 3 and 4, and 5 and 7 were proportionally pooled to create 3 samples per cow for lipidomic analysis (i.e., pool 1 = DIM 1 and 2; pool 2 = DIM 3 and 4; pool 3: DIM 5 and 7). Statistical analyses were performed using SAS v9.4 (SAS Institute Inc.) and least squares means adjusted for multiple comparisons using the Tukey-Kramer test. Comparisons for EarlyHp and LateHp were only performed on pooled samples from DIM 1 and 2 (i.e., before metritis diagnosis). EarlyHp cows had decreased concentrations of 9(S)-HOTrE compared with LowHp cows of DIM 1–2 pooled samples. LateHp cows had decreased concentrations of 9(10)-DiHOME compared with LowHp cows. Next, we sought to investigate whether cows classified as PersistentHp had time-dependent differences in oxylipin profile versus LowHp cows. PersistentHp cows had decreased concentrations of 19(R)-HETE compared with LowHp cows in a time-dependent manner (only in pooled samples from DIM 5 and 7). Our results identified oxylipins of interest that warrant further investigation to elucidate their in vitro and in vivo functions in the postpartum inflammatory process of dairy cows.